Stabilization of graphene quantum dots (GQDs) by encapsulation inside zeolitic imidazolate framework nanocrystals for photoluminescence tuning - Biswal, Bishnu P.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Banerjee, Rahul (Nanoscale, 2013)
Luminescent graphene quantum dots (GQDs) are encapsulated and stabilized in Zeolitic Imidazolate Framework (ZIF-8) nanocrystals. The GQDs are well confined due to the adsorption on the growing face of the ZIF-8 nanocrystals and have a profound effect on the shape of the nanocrystals from rhombic dodecahedron to spherical. Stabilizing GQDs inside the ZIF-8 nanocrystals results in tailoring of the photoluminescence emission (ca. 32 nm, bathochromic shift) of the GQD@ZIF-8 nanocrystal composite even after 3 months of aging under normal laboratory conditions. Also the water adsorption (at STP) capacity increased for the GQD@ ZIF-8 composite as compared to the pristine ZIF-8.

Sequential electrochemical unzipping of single-walled carbon nanotubes to graphene ribbons revealed by in situ Raman spectroscopy and imaging - John, Robin; Shinde, Dhanraj B.; Liu, Lili; Ding, Feng; Xu, Zhiping; Vijayan, Cherianath; Pillai, Vijayamohanan K.; Pradeep, Thalappil (ACS Nano, 2014)
We report an in situ Raman spectroscopic and microscopic investigation of the electrochemical unzipping of single-walled carbon nanotubes (SWNTs). Observations of the radial breathing modes (RBMs) using Raman spectral mapping reveal that metallic SWNTs are opened up rapidly followed by gradual unzipping of semiconducting SWNTs. Consideration of the resonant Raman scattering theory suggests that two metallic SWNTs with chiralities (10,4) and (12, 0) get unzipped first at a lower electrode potential (036 V) followed by the gradual unzipping of another two metallic tubes, (9, 3) and (10, 1), at a relatively higher potential (1.16 V). The semiconducting SWNTs with chiralities (11, 7) and (12, 5), however, get open up gradually at +/- 1.66 V. A rapid decrease followed by a subsequent gradual decrease in the metallicity of the SWNT ensemble as revealed from a remarkable variation of the peak width of the G band complies well with the variations of RBM. Cyclic voltammetry also gives direct evidence for unzipping in terms of improved capacitance after oxidation followed by more important removal of oxygen functionalities during the reduction step, as reflected in subtle changes of the morphology confirming the formation of graphene nanoribbons. The density functional-based tight binding calculations show additional dependence of chirality and diameter of nanotubes on the epoxide binding energies, which is in agreement with the Raman spectroscopic results and suggests a possible mechanism of unzipping determined by combined effects of the structural characteristics of SWNTs and applied field.
Keywords: density functional-based tight binding calculations; Electrochemistry; graphene; Raman spectral mapping; single-walled carbon nanotubes

Synergistic humidity-responsive mechanical motion and proton conductivity in a cationic covalent organic framework - Das, Gobinda; Shinde, Dhanraj B.; Melapurakkal, Amrutha; Shelke, V, Manjusha; Garai, Bikash; Bazin, Philippe; Blal, Abdelhafid Ait; Benyettou, Farah; Prakasam, Thirumurugan; Halim, Rasha Abdul; Ibrahim, Fayrouzabou; Sharma, Sudhir Kumar; et al. (CHEM, 2024)
Keywords: ACTUATORS; Crystalline; DRIVEN; SOFT